The Effect of Smasse In-Service Training on Performance of Mathematics in Selected Sendondary Schools in Kenya - Dennis, Nyamwange Nyamari; Wambua, Kyalo Benjamin; Peter, Opakas (European Scientific Journal, ESJ, 2017)
Over the years performance of mathematics at secondary level has dropped significantly causing a major concern to society. It is against this background that this study sought to investigate the effect of Strengthening Mathematics and Sciences in Secondary Education, In-Service Education Training project on performance of mathematics at Kenya Certificate of Secondary Examinations, with regard to the subject content, pedagogy/methodologies, attitude and teaching-learning material. The study area was in Kisii Central District in Kisii County. The sample size comprised of 20 secondary schools, 41 mathematics teachers and 380 students. Both probability and nonprobability Sampling techniques were adopted to determine sample size. Qualitative data were collected through interview and document analysis. Questionnaires were used to collect quantitative data from students, teachers of mathematics and Mathematics Head of Departments. Quantitative data were analyzed by both descriptive and inferential statistics (chi-square). Qualitative analysis involved categorization and development of themes. The research found out that Strengthening Mathematics and Sciences Secondary Education, In-Service Education Training project had significantly improved performance of mathematics. The study established that Strengthening Mathematics and Sciences Secondary Education, In-Service Education Training has changed attitude of teachers and students, improved Pedagogical Content Knowledge and Teaching/Learning Materials, and thus some improvement in performance of mathematics. The study will be useful to the mathematics teachers in evaluating their work against the SMASSE INSET methodologies in relation to their performance. The study will also be useful to DQASO’s for their supervision processes from one school to another. The findings should also help proponents of SMASSE INSET project to review their curriculum especially to incorporate more content coverage to add to the mastery of content of the mathematics teachers. The study recommends for further research on the relevance of subject content knowledge acquired by secondary mathematics teachers in the teachers training colleges and universities.